2017
DOI: 10.1016/j.toxlet.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Connexin hemichannel inhibition reduces acetaminophen-induced liver injury in mice

Abstract: Historically, connexin hemichannels have been considered as structural precursors of gap junctions. However, accumulating evidence points to independent roles for connexin hemichannels in cellular signaling by connecting the intracellular compartment with the extracellular environment. Unlike gap junctions, connexin hemichannels seem to be mainly activated in pathological processes. The present study was set up to test the potential involvement of hemichannels composed of connexin32 and connexin43 in acute hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 66 publications
1
21
0
Order By: Relevance
“…Indeed, to our knowledge connexin channels are the only channels inhibited by extracellular divalent cations, La 3+ and Gap27. Furthermore, we observed that extracellular ATP concentration increase in HLE-B3 cells in response to DCFS, an effect that was significantly reduced by CBX, which is consistent with ATP efflux through hemichannels (Kang et al, 2008;Maes et al, 2017). On the other hand, we found that exposure to LA increases HLE-B3 cells Etd + uptake rate, which also was prevented by La 3+ , CBX, and Gap 27.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, to our knowledge connexin channels are the only channels inhibited by extracellular divalent cations, La 3+ and Gap27. Furthermore, we observed that extracellular ATP concentration increase in HLE-B3 cells in response to DCFS, an effect that was significantly reduced by CBX, which is consistent with ATP efflux through hemichannels (Kang et al, 2008;Maes et al, 2017). On the other hand, we found that exposure to LA increases HLE-B3 cells Etd + uptake rate, which also was prevented by La 3+ , CBX, and Gap 27.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, high Cx43 immunoreactivity is seen around inflamed and necrotic areas in acute‐on‐chronic liver failure in rat . Interestingly, specific Cx32 and/or Cx43 hemichannel inhibition reduces levels of proinflammatory cytokines and alanine aminotransaminase after acetaminophen overdosing (Table ) . Recently, it has been shown that levels of hepatic Panx1 increase in acetaminophen‐overdosed mice (Table ).…”
Section: Pathophysiology Of Connexin and Pannexin (Hemi)channelsmentioning
confidence: 99%
“…Subsequent work showed that the peptide also selectively inhibited Cx43 hemichannels in astrocytes [ 121 ]. More recently, Gap19 was shown to reduce serum levels of pro-inflammatory cytokines in mouse models of acetaminophen-induced liver injury and non-alcoholic steatohepatitis [ 122 , 123 ]. Conversely, in a mouse model of sepsis, Gap19 was surprisingly found to increase macrophage hemichannel activity and decrease animal survival [ 118 ].…”
Section: The Intersection Of Hemichannels Inflammation and Breasmentioning
confidence: 99%